Museums in motion : an introduction to the history and functions of museums - Alexander, Edward P. (Edward Porter), 1907-2003; Alexander, Mary, 1946-; American Association for State and Local History (Lanham : AltaMira Press)
Includes bibliographical references (p. 323-331) and index.